Comparing the Accuracy of Patient-Perceived Fever, Manual Fever Checking, and Non-Contact Frontal Infrared Thermometer; A Cross-sectional Study - Shabani-Kakroudi, Moojan; Jalili, Mohammad; Meysamie, Ali Pasha; Akhgar, Atousa; Akbari, Hamideh; Zangi, Mahdi; Aligholi Zahraie, Mehrnoosh; Aqavil-Jahromi, Saeed; Eftekhari, Mohammad (Archives of Academic Emergency Medicine, 2026)
Introduction: Non-contact frontal infrared thermometers (NCFITs) have gained popularity following the COVID-19 pandemic, but their accuracy remains debated. This study compared the accuracy of three index tests of patient-perceived fever (PPF), manual fever checking (MFC) by emergency nurses, and NCFIT against tympanic thermometer (TT). Methods: This single center, diagnostic accuracy study evaluated adult patients in the triage area of the emergency department (ED) between May and September 2023. Five emergency nurses (ENs) examined patients using convenience sampling with index tests, followed by TT measurement for fever detection as standard test (T≥38°C). The sensitivity, specificity, positive and negative likelihood ratios (PLR and NLR) and accuracy, of PPF, MFC, and NCFIT in detecting the fever were measured and reported with 95% confidence interval (CI). The inter-rater reliability of ENs for MFC among 10 patients (outside the study) was 100%. Results: We included 279 patients with the mean age of 52.2 ± 16.98 years (51.97% male). TT identified 147 as febrile and 132 as non-febrile. The most sensitive index test was MFC, achieving 100% (95%CI: 97.5–100.0) sensitivity, 0 NLR, and 8.25 (95%CI: 5.7–12.1) PLR, with moderate accuracy (93.9% (95%CI: 89.9–96.0)). NCFIT demonstrated the lowest sensitivity (85.71% (95%CI: 78.9–90.9)) but the highest specificity (98.48% (95%CI: 93.6–99.5)) and accuracy (97.5% (95%CI: 93.1-99.8)). When the fever threshold for NCFIT was lowered to 37.5°C, sensitivity increased to 99% (95%CI: 97.4-99.9), NLR decreased to 0.01 (95%CI: 0-0.6), and PLR rose to 49.5 (95%CI: 20.8-90.2), while specificity remained at 98% (95%CI: 94-99.6). Conclusion: MFC/PPF could rule out fever but required NCFIT/TT to rule it in. However, NCFIT achieved the highest NLR and PLR when its fever threshold was set at 37.5 °C.